TEACHERS’ PERCEIVED ATTITUDES TOWARD THE IMPLEMENTATION OF 21ST CENTURY SKILLS AT PRIMARY SCHOOL - Utami, Luh Putu Restu Adi; Padmadewi, Ni Nyoman; Artini, Luh Putu; Dewi, Ni Luh Putu Eka Sulistia (Universitas Pendidikan Ganesha, 2021)
21st century education requires teachers to be able to understand the 21st century skills and apply them in daily classroom practice. Although necessary for teachers, research on investigating the teachers’ perceived attitudes toward the implementation of the 21st century skills for teaching English in primary schools in Bali is still limited. This study aimed to investigate primary school’s English teachers’ perceived attitudes toward the implementation of 21st-century skills. The design of this study was a sequential embedded mixed method with dominantly used qualitative design. This study used 3 English teachers and two headmasters from 2 primary schools in Tabanan regency as the subject. The data were collected by using a questionnaire and interview to gain the data of teachers’ perceived attitudes toward the implementation of the 21st century skills. From the data that have been obtained, primary English teachers gave positive attitudes toward 95,8% of the skills in the implementation of 21st century skills. The interview section showed that the teacher lacks understanding of 21st century skills because of a lack of in-depth information about 21st century skills. Moreover, the teachers have to be aware of 21st century skills in the assessment as one of the concepts that are adapted for Kurikulum 2013.